Tantangan dan Prospek Pendidikan Vokasi di Era Digital : Tinjauan Literatur - Riza Ubihatun; Aninda Ilmi Aliyya; Fardi Wira; Viby Izmi Ardhelia; Denny Oktavina Radianto (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
The integration of vocational education curriculum with industry needs is a crucial step in preparing graduates to face the evolving dynamics of the job market. Literature review highlights the importance of curriculum relevance to industry needs, encompassing contemporary skills such as artificial intelligence and robotics, in enhancing graduates' readiness to contribute to economic development. Collaboration between vocational education institutions and industries plays a key role in ensuring curriculum relevance. However, challenges such as inflexibility in the curriculum and resistance to change remain issues to be addressed. Ongoing evaluation is necessary to ensure the effectiveness of the curriculum in preparing graduates. Measures such as increased collaboration with industries, enhanced curriculum flexibility, and investment in vocational education infrastructure are key to improving curriculum integration. Thus, vocational education is expected to continue playing a crucial role in supporting sustainable economic growth.